Confluence of cultural traditions in the plains of the colombian caribbean. The case of the archaeological sites La Floresta and Macumba in Tolú Viejo (Department of Sucre) - Serna Ramírez, Aceneth (2018)
This article has been written from the archaeological findings of the sites La Floresta and Macumba (municipality of Tolú Viejo, department of Sucre, Colombia) and the tracking of the main documentary sources both chronicles of the sixteenth century and previous archaeological projects. It aims to show the confluence of two cultural traditions: the Zenú and Malibú groups located in the coastal lowlands of the Colombian Caribbean Region. This region, with its great rivers such as Magdalena, Sinú, San Jorge, Nechí and Cauca, has undoubtedly played an important role in the social dynamics of the Colombian territory. It has been the scene of the main settlement routes, natural communication routes and the ecosystems associated with them, they have served as food sources for both prehispanic and current inhabitants.